(untitled) (Anclajes, 2021)
Anclajes, from its beginnings and until today, has fostered the dissemination of articles and book reviews linked to descriptive linguistics, sociolinguistics and the historiography of the languages of Latin America. This paper reviews how the publication has witnessed, during the last twenty-five years, the advances and changes in research on Amerindian languages, cultures and literatures.